Sheikh Hamad Al-Jasser and the trips of Westerners to the Arabian Peninsula | الشيخ حمد الجاسر ورحلات الغربيين إلى الجزيرة العربية - Al Bikai | البقاعي, Muhammad Khair | محمد خير (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
The research is based on the idea that the word “journey” represents the key to the life of Sheikh Al-Jasser, whose life and deeds were a permanent and continuous journey, and it attempts to investigate the manifestations of that representation through the Sheikh’s speech and sayings. The research assumes that Al-Jasser had two types of journeys: the real journeys, which he took to search for Heritage, hospitalization, or other life reasons. And a metaphorical journey that took place in the depths of books and manuscripts, reviewing them, assessing their contents, and sometimes re-publishing them. | ينطلق البحث من فكرة فحواها أن مفردة الرحلة تمثل مفتاح حياة الشيخ الجاسر، الذي كانت حياته وأعماله رحلة دائمة ومستمرة، ويحاول تقصي مظاهر ذلك التمثيل من خلال حديث الشيخ وأقواله، ويفترض البحث أن لدى الجاسر نوعين من الرحلات: الرحلات الحقيقية، التي قام بها للبحث عن التراث، أو للاستشفاء، أو لأسباب حياتية أخرى. ورحلة مجازية كانت في بطون الكتب والمخطوطات يراجعها، ويقيم أودها، ويعيد نشرها في بعض الأحيان